HUBUNGAN UMUR, PENDIDIKAN, PEKERJAAN, PARITAS DAN RIWAYAT MASTITIS DENGAN KEJADIAN MASTITIS - Anggun Hatto Hanti; Lina Handayani; Azidanti Saufi (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: The national coverage of exclusive breastmilk did not reach its target in 2014. One reason behind this was due to the swelling of the breast to mastitis condition. Hence the baby was not getting enough breastmilk. World Health Organization WHO estimates the mastitis case between 2.6 and 33 %, with global prevalence around 10% of all breastfeeding women. In 2014, Panembahan Senopati Bantul Yogyakarta Hospital documented 5.3% women with mastitis and 4.2% in 2015. Objective: This research aims to evaluate the correlation of ages, education, employment status, parity, and mastitis history with mastitis case in Panembahan Senopati Bantul Yogyakarta Hospital.Methods: This research was an observational analytic with a case-control design. Data analytic was performed using the Chi-Square test. Results: The results of bivariate analysis showed that age (OR = 0.673; 95% CI; 0.345-1.314), education (OR = 1.288; 95% CI; 0.678-2.44), employment status (OR = 1.368; 95% CI; 0.749 -2.497), and parity (OR = 0.829; CI 95%; 0.455-1.511) did not have a significant correlation with the incidence of mastitis, but the history of mastitis showed a significant association with the incidence of mastitis (OR = 2.280; 95% CI; 1.112-1.674 ). Conclusion: There was a correlation between the history of mastitis with the recurrence of mastitis in Panembahan Senopati Bantul Yogyakarta Hospital.